Profiles and roles of TV anchorpersons in a disaster context: conceptual proposal from the case of the 27F earthquake in Chile - Grassau, Daniela (2019)
: A conceptual proposal of the profiles and roles that communicators can assume during the coverage of a disaster was developed based on the discourse analysis of the interventions made by the anchorpersons of the Chilean broadcast TV newscasts during the 8.8 Mw earthquake of 2010. This was used to identify and describe the presence of three potential profiles: informative (descriptive presentation of the content), judgmental (a judgment position prevails), and of dialogue with the audience (direct message to viewers). The data shows that the predominant profile was the informative one, whereas the judgmental appears strongly during the first days of disaster and then weakens, and that the dialogue with the audience is strengthened from the third day. These results open a line of research on the role of the media to promote the spontaneous recovery of a population faced with a trauma.